The Assessment of non-English Lecturer English Skills through TOEFL Training and Test at a Private College in Jakarta - Octa Pratama Putra; Fitriyah Fitriyah; Herlin Widasiwi Setianingrum; Sufi Alawiyah (UICELL, 2019)
The lecturers are supposed to increase their English competence which is indicated by their TOEFL scores. This research is aimed to know the measurement of English skills toward the non-English lecturers from different background by joining the TOEFL training and test. There are twenty selected-lecturers to join it at one of Private colleges around Jakarta and due the requirement of lecturers’ certification. It has Listening, Structure-Written Expression, and Reading Comprehension. The research form is done by providing a field research; by two matters of obtaining the data, they are: by using written test and giving observation. While for the assessment, it has two steps; the first is providing the lecturers to do the pretest which purposes to know the current level of TOEFL mastery and the second is giving the post-test, which reflects to know the final comprehension after joining the TOEFL training. Before it, the lecturers have the opportunity to have the TOEFL training for about two months intensively, thrice of sessions within a week. The result, mostly, the lecturers have the predicate of Beginner in achieving their TOEFL final score through the training. The mean score points out 421. Keywords: TOEFL, Assessment, Mastery, Pretest, Post-test.